Near Infrared Imaging Technology and Latex Imaging of Superficial Veins in Rats Investigation using Methods - Karaavcı, Funda Aksünger; Karan, Meryem (My University, 2024)
Near-infrared imaging technology devices create a real-time image of the 8–15 millimeters (mm) peripheral veins under the skin. In this study, 15 Wistar Albino rats were used. Aim of this study was to reveal whether the vein-viewer device (Accuvein av 400) can visualize thoracic and pelvic limb superficial veins in rats. Firstly, vein viewer imaging of the limbs of the materials was performed and the findings were recorded. Afterwards, the materials were dissected by applying the latex injection method to the same animals and the results were evaluated comparatively. In rats, it was found that vena cephalica starts as two branches, the first branch is in the middle 1/3 of the neck length and the second branch originates from v. jugularis externa at the entrance to the thoracic cavity. While the run of vena cephalica in regio colli could not be viewed with the vein viewer device, it was possible to view it down from the regio brachii. It was observed that v. saphena medialis, and v. saphena lateralis which are the superficial veins of the pelvic limb, viewed with the vein viewer device throughout their run. Given the findings of this research this device may be considered as an alternative method for imaging superficial veins in animals. Additional morphological and clinical studies could show the techniques efficacy in animals.
Keywords: Rat; Latex; near-infrared-imaging; vein; vein imaging